Use of Finite Point Method for Wave Propagation in Nonhomogeneous Unbounded Domains - Moazam, Saeid; Çelikağ, Mürüde (Hindawi Publishing Corporation, 2015)
Wave propagation in an unbounded domain surrounding the stimulation resource is one of the important issues for engineers. Past literature is mainly concentrated on the modelling and estimation of the wave propagation in partially layered, homogeneous, and unbounded domains with harmonic properties. In this study, a new approach based on the Finite Point Method (FPM) has been introduced to analyze and solve the problems of wave propagation in any nonhomogeneous unbounded domain. The proposed method has the ability to use the domain properties by coordinate as an input. Therefore, there is no restriction in the form of the domain properties, such as being periodical as in the case of existing similar numerical methods. The proposed method can model the boundary points between phases with trace of errors and the results of this method satisfy both conditions of decay and radiation.
The file in this item is the publisher version (published version) of the article.
Keywords: MECHANICS, ELEMENT-METHOD; MATHEMATICS, INTERDISCIPLINARY APPLICATIONS, ENGINEERING; MULTIDISCIPLINARY, Algorithms, Mathematical research; Fixed point theory, Wave propagation, Analysis,; Methods, Usage, QA1-939,